The Role of Motivation Towards Sports Participation among Student-Athletes - Richardson, Donnamey; Ompoc, Harlyn Mae S. (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
This study aimed to investigate the role of motivation in the sports participation of student-athletes in Iligan City, Philippines. The Motivation for Sports Measure–Revised (MSM-R), adapted from the Motivation for Physical Activity Measure-Revised developed by Ryan et al. (1997), was utilized to assess motivation, while the Sports Participation Model Questionnaire (SPMQ) developed by Aicenena (2012) was employed to evaluate athletes' sports involvement. A total of 1015 college student-athletes from various Colleges and Universities in Iligan City participated by completing a series of questionnaires pertaining to motivation and sports participation. Analysis of the motivation subscales revealed that appearance, competence, and social interaction exhibited significant associations with sports participation among the student-athletes. Conversely, interest/enjoyment and fitness did not demonstrate a significant relationship with sports participation. These findings suggest that appearance, competence, and social interactions are the primary drivers motivating student-athletes to engage in sports activities. Hence, the findings of this study indicate that student-athletes participate in sports not primarily out of interest, enjoyment, or fitness concerns, but rather to enhance their physical attractiveness and social interactions. This underscores the importance of understanding motivational factors influencing sports participation and their implications for promoting and sustaining engagement among student-athletes.